The Ameliorative Effect of Apigenin in Plectranthus amboinicus Lour Spreng in the Treatment of Hepato-renal Carcinogenesis Induced Benzo(a)pyrene - Melva Silitonga; Hendro Pranoto; Erlintan Sinaga; Feimmy Ruth Pratiwi Sipahutar; Adriana Yulinda Dumaria LumbanGaol; Fajar Apollo Sinaga (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Benzo(a)pyrene (B(a)P) is the major cause of hepato-renal carcinogenesis. Apigenin in Plectranthus amboinicus (EPA), has indicated some biological activities such as antioxidant and antimutagenic activity. The aim of this study is to investigate the potential of apigenin in EPA as anti-cancer against chronic hepatorenal damage exposed to B(a)P. The rats of 4 groups (n=6) were divided as follows: Group I (P0) was given food and water ad-libitum; Group II (PB) was administered orally B(a)P 2 mg/kg BW; Group III (PB+E) received orally B(a)P 2 mg/kg BW and EPA 500 mg/kg; Group IV (PE) was administered orally EPA 500 mg/kg BW. The therapeutic effect of EPA was explored using network pharmacology and molecular docking. The results showed that Group III could significantly improve (P < 0.05) the hepatorenal function parameter, including DNA concentration. SGPT, SGOT, blood urea nitrogen, and creatinine compared to those treated with B(a)P. The outcome data pharmacology revealed 6 targets could be the main core target. The good binding affinity indicated Apigenin docked to AKT1 protein with -10.00 kcal/mol relevant to Doxorubicin as control drug. Our results provide a new insight of apigenin in EPA potentially suppressing the regulation of chemical carcinogenesis by B(a)P.